2021
DOI: 10.1007/s11250-021-02974-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of flaxseed and flaxseed oil supplemented in caiman diet on meat fatty acids

Abstract: Increasing polyunsaturated or long-chain fatty acids in meat for human consumption improves both nutritional quality and consumer perception. The increase could occur through the addition of rich sources of omega-3 fatty acids (such as axseed or axseed oil) to the animal diet. The aim of this study was to evaluate the effects of dietary supplement with two presentations of ax (crushed seeds or oil) on the change of FA content in two cuts of caiman meat (tail and neck). We measured fatty pro le in two different… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Colorimetry analysis showed no difference between the two smoking methods, with both of them shown average luminosity (L*) 51.94, a red intensity (a*) 17.85, and a yellow intensity (b*) 23.75 (Table 3). Although there is no literature regarding the colorimetry of smoked-breaded products, when compared with traditional chicken nuggets, this product shows a higher intensity of red (17.85 against 2.08) and yellow (23.75 against 12.42), with a lower luminosity (51.94 against 60.99), making it slightly darker and with attractive color [20,21]. Microbiological analysis of the smoked-breaded restructured (Table 4) followed the standards established by the National Health Regulatory Agency (ANVISA), which requires MPN g -1 <3 for coliforms at 35º and 45º C, absence of Salmonella ssp.…”
Section: Resultsmentioning
confidence: 99%
“…Colorimetry analysis showed no difference between the two smoking methods, with both of them shown average luminosity (L*) 51.94, a red intensity (a*) 17.85, and a yellow intensity (b*) 23.75 (Table 3). Although there is no literature regarding the colorimetry of smoked-breaded products, when compared with traditional chicken nuggets, this product shows a higher intensity of red (17.85 against 2.08) and yellow (23.75 against 12.42), with a lower luminosity (51.94 against 60.99), making it slightly darker and with attractive color [20,21]. Microbiological analysis of the smoked-breaded restructured (Table 4) followed the standards established by the National Health Regulatory Agency (ANVISA), which requires MPN g -1 <3 for coliforms at 35º and 45º C, absence of Salmonella ssp.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate physiological condition, we select unsaturated FA, mainly essential FA (EFA), because they best reflect the FA composition of the diet and/or food resources of animals and may allow us to assess the possible energy investment in reproduction (Speake et al, 1999; Labaque et al, 2013; Leiva et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…We chose to use muscle tissue FA as an indicator of female nutritional status since it was impossible to obtain tissue samples of visceral fat or other sources of body fat without jeopardizing the health of the animals captured. Previous studies on captive Caiman latirostris have shown that the muscle FA profile is related to diet in previous months (Piña et al, 2016;Leiva et al, 2021). Therefore, the information would allow us to evaluate the obtention of energetic resources by females months prior to sampling, which coincide with the months in which the females carry out the process of assigning resources to the progeny (vitellogenesis).…”
Section: Body Attributes: Body and Physiological Conditionmentioning
confidence: 99%
“…In this context, numerous studies show the positive nutritional characteristics of the meat and fat of some other reptile species. For example, both Caiman latirostris and Iguana iguana meats have a high protein percentage and can be considered as an alternative source of animal protein with good nutritional quality for human consumption [6][7][8][9][10][11]. There are also reports on reptiles' fat, such as C. latirostris and S. merinae, which mention their potential value for food since they contain a high percentage of n-3 polyunsaturated fatty acids and recommended nutritional indexes [12,13].…”
Section: Introductionmentioning
confidence: 99%